Animacy norms for 224 European Portuguese concrete words - Félix,Sara B. (2020)
Words are frequently used, for example, as stimuli in cognitive and linguistic research. Considering that there are various psycholinguistic variables known to influence word processing (e.g., frequency, concreteness), it is important to control for those variables. Recently, it has been reported that animacy (the characteristic of being a living/animate or a non-living/inanimate entity) also affects various cognitive and linguistic processes. In fact, animacy has been found to be one of the best predictors of free recall. However, animacy is still an uncontrolled variable in most studies and information about this variable is still, for the most part, absent. In this study, we provide animacy norms for a set of 224 European Portuguese concrete words. Such data should provide Portuguese researchers a helpful tool to start considering this dimension in a systematic way in their research.